Faktor-faktor yang Mempengaruhi Volume Perdagangan Saham Menggunakan Multivariate Adaptive Regression Splines - Otok, Bambang Widjanarko; Guritno, Suryo; Subanar, . (Jurnal Widya Manajemen & Akuntansi, 2006)
This research aims to know influence the Composite Index on price Share (IHSG), Right Issue, Dollar Rate and interest rate storey level of Singapore International Bonk Offered Rate (SIBOR) to on trading volume stock in Effect Exchange Surabaya. This matter ii- oftentimes studied with regression analysis, and at this article introduce approach which relative n"erly in oy regression analysis that is Multivariate Adaptive Regression Splines (MARS). Modet U)nS, a model selection of MARSwith metho'l of stepwise. Forward Stepwise conducted to get afunction with amount of maximum basis .function. To .fulfitl conception parsemony lsimple i modet) conducted by bachtard stepwise lhat is cho.sening yielded basis .function of forwaid srepwise by minimizing value of Ceneralized Cross Validation (GCn. Result of research show with approach of MARS, important variable in influencing volume commerce of share is Right Issue with importance storey level t00%o, price Index Share Aliance (IHSG) with importance storey tevet 38,986%, and Dollar Rate with importance storey level equal to 6,477%. Ll/hile a SIBOR not such an important variable in influencing commerce volume. Right Issue happened change of volume commerce o f share at value qf , = O i-t tOOOE+10 and t = 0.63000E+ll. The change have tendencl,g o up slrnlt,front | = 20024704 .r.re.s/ .s= 0. l1l000E+10 and have tendency go up incisively.fron t : 0.ttt000E+10 up to t : 0.63000E+I 1.